Big - Harrison, Vashti (New York : Little, Brown and Company, 2022)
Praised for acting like a big girl when she is small, as a young girl grows, 'big' becomes a word of criticism, until the girl realizes that she is fine just the way she is.
With fold-out pages.
1.5
K-3
Keywords: Physical-appearance-based bias -- Juvenile fiction; Growth -- Juvenile fiction; Identity (Psychology) -- Juvenile fiction; Self-acceptance -- Juvenile fiction; Physical-appearance-based bias -- Fiction; Growth -- Fiction; Identity -- Fiction; Self-acceptance -- Fiction; Body size -- Juvenile fiction